Pengaruh Motivasi Kerja dan Pelatihan Kerja terhadap Kinerja Karyawan PT Yageo TMSS Indonesia - Marbun, Ajiza; Purba, Daris (Program Studi Manajemen FEBM UMRAH, 2026)
In the competitive industrialization era, employee performance is a crucial asset determining the success of manufacturing companies. However, in work environments with strict Standard Operating Procedures (SOP) and a dominance of middle-level contract workers, the effectiveness of conventional motivation on productivity becomes a questionable issue. This study aims to analyze the partial and simultaneous effects of work motivation and job training on the performance of operational employees at PT Yageo TMSS Indonesia. The research utilized a quantitative explanatory method, employing purposive sampling involving 104 respondents. Primary data were collected through questionnaires and analyzed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) approach via SmartPLS 4. The results reveal that, partially, work motivation has no significant effect on employee performance, indicating that in a mechanical work system, psychological impulses do not automatically convert into physical output. Conversely, job training exerts a highly dominant and positive effect on performance improvement. Simultaneously, the combination of motivation and training contributes to 60.5% of the employee performance variance. In conclusion, the performance stability of contract workers in the labor-intensive manufacturing sector is determined more by the technical skills acquired from training than affective aspects.